2011
DOI: 10.1007/s00442-010-1899-3
|View full text |Cite
|
Sign up to set email alerts
|

Large herbivores may alter vegetation structure of semi-arid savannas through soil nutrient mediation

Abstract: In savannas, the tree–grass balance is governed by water, nutrients, fire and herbivory, and their interactions. We studied the hypothesis that herbivores indirectly affect vegetation structure by changing the availability of soil nutrients, which, in turn, alters the competition between trees and grasses. Nine abandoned livestock holding-pen areas (kraals), enriched by dung and urine, were contrasted with nearby control sites in a semi-arid savanna. About 40 years after abandonment, kraal sites still showed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
104
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 64 publications
(132 reference statements)
7
104
0
1
Order By: Relevance
“…Additionally, Acacia sapling growth rates were higher in nutrient-rich soils when compared to growth in nutrient-poor grassland soils (Wakeling et al 2010). In contrast, certain studies have found that abundant soil nutrients improve herbaceous productivity which in turn suppresses tree sapling establishment (Cohn et al 1989, Kraaij and Ward 2006, van der Waal et al 2011). Although we did not find any significant nutrient-grass interactive effect on sapling growth, the negative effects exerted by grasses were greater than the positive effects of nutrients (see also Kambatuku et al 2013 for Acacia mellifera).…”
Section: Notesmentioning
confidence: 96%
“…Additionally, Acacia sapling growth rates were higher in nutrient-rich soils when compared to growth in nutrient-poor grassland soils (Wakeling et al 2010). In contrast, certain studies have found that abundant soil nutrients improve herbaceous productivity which in turn suppresses tree sapling establishment (Cohn et al 1989, Kraaij and Ward 2006, van der Waal et al 2011). Although we did not find any significant nutrient-grass interactive effect on sapling growth, the negative effects exerted by grasses were greater than the positive effects of nutrients (see also Kambatuku et al 2013 for Acacia mellifera).…”
Section: Notesmentioning
confidence: 96%
“…Terrestrial herbivores typically do not graze and excrete randomly, but are attracted to landscape features, such as nutrient-rich areas with high food quality, resulting in a net import of nutrients and creating nutrient hotspots in the landscape. At the same time, large parts of the landscape with poorer quality vegetation experience a net removal of nutrients (McNaughton et al, 1997;Augustine et al, 2003;van der Waal et al, 2011). Water bodies may also induce spatial patterns; semi-aquatic herbivores such as hippopotamus, beaver or water birds can transport nutrients across ecosystem boundaries and thus strongly impact nutrient redistribution Subalusky et al, 2015;Bakker et al, 2016).…”
Section: Applying Rule 2 To Terrestrial Ecosystemsmentioning
confidence: 99%
“…Grasses often compete intensely with young trees (e.g., van der Waal et al 2009;Cramer et al 2010). Glades in our study site typically have very high grass cover (Veblen 2008;Porensky 2011), creating an environment in which grass competition may be severe enough to kill young trees (e.g., van der Waal et al 2011). Areas between nearby glades have unusually low cover of dense glade grasses, which may release young trees from competition and help explain increased tree densities between nearby glades (Porensky 2011).…”
mentioning
confidence: 98%
“…Herbivory has major impacts on woody cover in savanna ecosystems (Pellew 1983;Augustine and McNaughton 2004;Goheen et al 2010) and could play a particularly important role in determining woody cover patterns associated with glades, where use by mid-sized, mixed-feeder herbivores is elevated (Young et al 1995;van der Waal et al 2011). Herbivore preference may lead to elevated browsing pressure and reduced tree survival or growth within glades, particularly for young trees (seedlings and saplings) (Goheen et al 2004;Midgley et al 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation